Determinants of Cashless Transaction Adoption: Evidence from Commercial Bank Customers in Pokhara - Amgain, ushpa Nidhi; Bishokarma, Anita (Journal of Interdisciplinary Studies, 2026)
This study aims to investigate the determinants influencing the adoption of cashless payments in commercial banks in Nepal, with special reference to digital payment usage in Pokhara Metropolitan City. The study employed a quantitative study design that involved both descriptive and causal comparative research design. A structured questionnaire, using a 5-point Likert scale. Data were collected from 450 respondents and the measure of perceived ease of use, perceived usefulness, and personal innovativeness. Respondents were selected through convenience sampling of markets, learning institutions, local businesses and financial service centers. Data were analyzed using descriptive statistics, correlation analysis and multiple regression to examine the relationship between independent variables and cashless transaction adoption. The results showed that the three determinants have a positive influence on the adoption of cashless transactions. Perceived usefulness was significant predictor among them, which indicates that the users are more inclined to adopt digital payment system. Perceived ease of use and personal innovativeness had a significant positive influences on cashless transaction adoption. The implication of the study are relevant for banks and financial institutions(BFIs), policymakers and technology providers on how to facilitate the usability and innovation of digital payment system. Future research can examine how emerging technologies such as blockchain and biometric authentication influence the adoption of cashless payments. In particular, digital financial literacy should be incorporated as a moderating variable to provide deeper understanding of adoption cashless transactions over time.